Ontological Aspects of Quantum Field Theory - Kuhlmann Meinard (World Scientific, 2002)
Quantum field theory (QFT) provides the framework for many fundamental theories in modern physics, and over the years there has been growing interest in its historical and philosophical foundations. This anthology on the foundations of QFT brings together 15 essays by well-known researchers in physics, the philosophy of physics, and analytic philosophy. Many of these essays were first presented as papers at the conference "Ontological Aspects of Quantum Field Theory", held at the Zentrum fur interdisziplinare Forschung (ZiF), Bielefeld, Germany. The essays display cutting-edge work on ontological aspects of QFT, including: the role of measurement and experimental evidence; corpuscular versus field-theoretic interpretations of QFT; the interpretation of gauge symmetry; and localization. This text should be suitable for readers with an interest in the foundations of quantum physics, including physicists, philosophers and historians of physics, as well as general readers interested in philosophy or science.